PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP NILAI PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA PERIODE 2016-2020 - Samuel Kevin Jasa Nathanael Sianipar (2023)
Investors' perceptions of a company's level of success are frequently reflected in the stock price, which ultimately influences the value of the company. As a result, the value of the company is of concern to a number of parties, including investors. As a result, the goal of this study is to look at how leverage and profitability affect firm value in textile and apparel companies listed on the Indonesia Stock Exchange from 2016 to 2020. This quantitative study makes use of secondary data gathered from www.idx.co.id. The research sample, which included data from ten different businesses, was selected using the purpose sampling method. Multiple linear analysis techniques were used for the data analysis. According to the findings of this research, the leverage variable (DER) has a positive and significant impact on the value of textile and apparel businesses that are listed on the Indonesia Stock Exchange. That is, the company's value increases proportionay to its level of leverage. However, firm value is unaffected by the profitability variables (ROE and ROA). This implies that the degree of organization productivity doesn't essentiay influence organization esteem in the material and piece of clothing area. Investors and other market participants can learn a lot from these findings about the factors that can affect a company's value in the textile and clothing industry. When determining a company's potential to be worth a lot of money, investors may look at the amount of leverage. Then again, organization the executives in this area can utilize this finding to focus on their influence the board fuy intent on expanding firm worth.